Vera, or faith : a novel - Shteyngart, Gary, 1972- (Random House, 2025)
"The Bradford-Shmulkin family is falling apart. A very modern blend of Russian, Jewish, Korean, and New England WASP, they love one another deeply but the pressures of life in an unstable America are fraying their bonds. There's Daddy, a struggling, cash-thirsty editor whose Russian heritage gives him a surprising new currency in the upside-down world of twenty-first-century geopolitics; his wife, Anne Mom, a progressive, underfunded blue blood from Boston who's barely holding the household together; their son, Dylan, whose blond hair and Mayflower lineage provide him pride of place in the newly forming American political order; and, above all, the young Vera, half-Jewish, half-Korean, and wholly original. Observant, sensitive, and always writing down new vocabulary words, Vera wants only three things in life: to make a friend at school; Daddy and Anne Mom to stay together; and to meet her birth mother, Mom Mom, who will at last tell Vera the secret of who she really is and how to ensure love's survival in this great, mad, imploding world"--